The factors affecting the standard of reasonableness to determine the negligence in the English law. A comparative analytical study with the Iraqi civil law - علي, يونس صلاح الدين (Journal of Legal Sciences, 2019)
The Standard of reasonableness is considered as one of the objective standards adopted by the English Common law, to determine the standard of the care to be taken by the debtor of the obligation. And to ascertain the realization of the civil liability of negligence, the materialization of which requires four conditions. That is to say,  the imposition of the duty of care to the defendant, the beach of the duty of care, the damage befalling the plaintiff, and the causation or causal link between the tort of negligence and the damage.  It is also worth-bearing in mind that the forms of the  Standard of reasonableness are variate in the English law to meet the different circumstances arising from the variation of the factors affecting the standard. Whereas the Iraqi Civil law No. (40) of 1951 regulated also the Standard of reasonableness, and determined it by the reasonable person devoid from his or her internal personal circumstances, and surrounded by the same extermal circumstances of the wrongful act doer.